The Effectiveness of Laws and Policies on Domestic Violence Regarding Men - Karungi Irene Kemigisa (Uganda Christian University, 2024)
This paper discusses the effectiveness of the laws and policies on domestic violence regarding men. There is an increase of reported cases of domestic violence by male victims to the various organizations with authority to handle the matters like the police stations, and non-governmental organizations among others. The thesis further discusses the various laws both national and international on domestic violence regarding men as well as the national policies and the legal institutions that uphold the laws and policies. The paper also discusses the causes, effects of domestic violence, the limitations of why men remain in those violent relationships, summaries and recommendation.